Antecedents of Student's Behavioral Intentions in Higher Education Institutions - Surour Hamad Binnawas, Musabeh; S.A. Khalifa , Gamal; Bhaumick, Amyia (International Journal of Psychosocial Rehabilitation, 2020)
The primary objective of this study was to identify the nature of the relationship between service quality, customer satisfaction, and behavioral intention. The specific objectives of the study were to determine the dimensions of holistic approach service quality that influence students behavioral intentions; establish the difference in service quality perception amongst university students; determine the relationship between service quality and perceived value; determine the relationship between service quality and customer satisfaction; establish the relationship between perceived value and customer satisfaction; and assess the extent to which student satisfaction and perceived value mediate the relationship between service quality and behavioral intentions. The research hypotheses were derived from the research objectives. A positivist paradigm guided the study.